Antibacterial and antispore activities of crude extract and bioactive compounds of Piper cubeba L. berries against Bacillus sp. and application of the extract for food preservaton - Alqadeeri, Fatimah Khalleefah (2019)
In the food industry, the Bacillus species, in particular, is known as organisms that cause foodborne diseases and food spoilage. Bacillus species are produce of spores and many of the spores of the Bacillus species have been shown to be resistant to heat, radiation, and disinfectants. A previous study has shown that crude extracts of tailed pepper (Piper cubeba L.) have potential antimicrobial activities against some of Bacillus species. The present study aims to analyse the antibacterial and antispore activities of Piper cubeba L. berries extracts on the vegetative cells and spores of Bacillus cereus ATCC33019, B. subtilis ATCC6633, B. pumilus ATCC14884, and B. megaterium ATCC14581. Results showed that exposing of Bacillus sp. to P. cubeba L. extract and its compounds resulted in an inhibition zone with a large diameter which ranged between 9.50 to 11.40 mm for the extract and 7.21 to 9.61 mm for the compounds. The MIC of the extract ranged between 0.156 – 0.313 mg/mL and the MBC at 2.5 mg/mL. Moreover, for the compounds the MIC range was between 63.0 to 125.0 µg/mL and MBC at 250.0 to 500.0 µg/mL against Bacillus sp. The time-kill curve plots showed that exposing Bacillus sp. to a concentration of 8× MIC for a period of four hours resulted in the death of all cells. The values of MIC and MBC showed a fluctuating trend when the bacteria were exposed to P. cubeba L. extract treated with different temperature in comparison to untreated extract. Generally, the pH altered extracts caused a variation in the MIC and MBC values of the Bacillus sp. The effect of using varying concentrations of extracts and compounds against the Bacillus sp. spores for varying periods of incubation were determined. Glutaraldehyde, which is a chemical sporicidal agent, was used as a positive control. P. cubeba L. extract at a concentration of 1.0% inactivated more than 3-Log10 (90.99%) of the Bacillus sp. spores after an incubation period of four hours, and all the spores were killed at a concentration of 2.5%. The image of scanning electron microscope showed that the structure of spores were destroyed after treatment with 1% P. cubeba L. extract for one hour. The major volatile compounds, as determined using GC-MS, are β-cubebene, cubebol, α-copaene, α-cubebene, caryophyllene, 9,12-octadecadienoic acid, β-asarone, and germacrene-D. The non- volatile compounds identified through LC-MS are gallic acid, quinic acid, asaronaldhyde, epicatechin, clusin, cubebininolide, hemiarensin, β- asarone, hinokinin, ellagic acid, myricetin, and β-cubebene. The identified phytochemical compounds are similar with those in the literature and MS/MS databases. β-Asarone, asaronaldehyde, cubebin mixture and linoleic acid were successfully isolated and identified from the methanol extract of P. cubeba L. In general, a decrease of 3 Log10 of Bacillus sp., total plate count, E. coli and coliform bacteria on the tofu sample was observed when these bacteria were exposed to 0.50% (v/v) P.cubeba L. extract. In conclusion, P.cubeba L. extracts and its compounds show a promising potential of antibacterial and sporicidal activities against the Bacillus sp. and thus can be developed as an anti-Bacillus agent.